2015
DOI: 10.1590/01000683rbcs20140342
|View full text |Cite
|
Sign up to set email alerts
|

Nodulações e Produtividades de Grãos de Feijoeiros diante da Adubação Nitrogenada ou da Inoculação com Rhizobium Freirei

Abstract: reSUmOO conhecimento das respostas de feijoeiros em razão da adubação nitrogenada ou da inoculação das sementes com rizóbios pode direcionar seus cultivos para diferentes nichos de mercado, em níveis tecnológicos diversos. Foram avaliadas as nodulações das raízes e as produtividades de grãos de 10 cultivares de feijão diante da adubação nitrogenada e da inoculação das sementes com Rhizobium freirei, objetivando-se identificar em, termos de produtividades de grãos, as mais eficientes e responsivas à adubação ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
4
1
2
Order By: Relevance
“…There was no difference between the cultivars relative to the relative efficiency (RE), varying between 71.46 and 128.83%. Results similar to those found by Chagas Junior et al (2010), who did not obtain significance for RE when testing different cultivars, strains and nitrogen fertilization, while Yagi et al (2015) found ER of beans varying between 91 and 113%, while cultivars inferior to 100% were classified as efficient and responsive only to nitrogen fertilization.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…There was no difference between the cultivars relative to the relative efficiency (RE), varying between 71.46 and 128.83%. Results similar to those found by Chagas Junior et al (2010), who did not obtain significance for RE when testing different cultivars, strains and nitrogen fertilization, while Yagi et al (2015) found ER of beans varying between 91 and 113%, while cultivars inferior to 100% were classified as efficient and responsive only to nitrogen fertilization.…”
Section: Resultssupporting
confidence: 87%
“…In a study by Chekanai et al (2018), it demonstrated that there are improved bean cultivars responsive to rhizobium inoculation, and there are soils that are not responsive to this practice, especially those that are degraded. Yagi et al (2015) concluded that there are differences between commercial bean cultivars, with more efficient cultivars in the BNF in the presence of strains of native or exogenous rhizobia, while other cultivars are only responsive to nitrogen fertilization. This fact may have occurred with the cultivar Strike, which was not able to perform satisfactory nodulation.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen fertilization is detrimental to nodulation of common bean as shown by a study of response to inoculation in greenhouse [19] and field experiments [24] with different cultivars with a lower number of nodules. Field evaluation at Popayan with soil having high organic matter and high N availability reduced the amount of nitrogen derived from the atmosphere by biological fixation [25].…”
Section: Treatmentsmentioning
confidence: 99%
“…Essa redução é catalisada pela enzima nitrato-redutase nas células das raiz, embora as células de outros tecidos das plantas também possuam esta capacidade. A síntese da maior parte dos compostos orgânicos ocorre nas folhas (YAGI et al, 2015).…”
Section: Introductionunclassified